Intercultural Communicative Competence: Current Trends and Critical Dimension - Jacqueline García Botero; Margarita Alexandra Botero Restrepo; Cristian Camilo Reyes-Galeano; Yeray González-Plasencia (Philologia Hispalensis)
This article reports a systematic review of Intercultural Communicative Competence (ICC) in the field of foreign language teaching and learning with the aim of identifying tendencies in ICC research. Based on the PRISMA methodology (Urrútia & Bonfill, 2010), there was conducted an analysis of 79 research and reflection articles written between 2010 and 2022 which met all the criteria established in a search protocol. The search was developed in two phases. The first phase places emphasis on identifying various trends regarding ICC and the second one focused on the critical dimension of ICC. The analysis of all the studies lead to the identification of several challenges that could be assumed from future researchers: approaching ICC from a critical perspective, implementing innovative strategies for the development of ICC, analyzing ICC into policies and curriculums. The foray into this field broadens the view of what language teaching should be in the education of tomorrow.